Tackling Problems of Marker-Based Augmented Reality Under Water - Čejka, Jan; Liarokapis, Fotis (My University, 2020)
Underwater sites are a harsh environment for augmented reality applications. Divers must battle poor visibility conditions, difficult navigation, and hard manipulation with devices under water. This chapter focuses on the problem of localizing a device under water using markers. It discusses various filters that enhance and improve underwater images and their impact on marker-based tracking. Then, it presents different combinations of ten image-improving algorithms and four marker-detecting algorithms and tests their performance in real situations. All solutions are designed to run real-time on mobile devices to provide a solid basis for augmented reality. The usability of this solution is evaluated on locations in the Mediterranean Sea. Results show that image improving algorithms with carefully chosen parameters can reduce the problems with underwater visibility and enhance the detection of markers. The best results are obtained with marker detecting algorithms specifically designed for marine environments.
Keywords: Underwater sites; Augmented reality